2007
DOI: 10.1007/s10886-007-9262-9
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific Expression of Major Urinary Proteins in the House Mice (Mus musculus musculus and Mus musculus domesticus)

Abstract: The analysis of expression of pheromone-carrying major urinary proteins (MUPs) from two subspecies of house mice (Mus m. musculus, Mus m. domesticus) was studied. It has been previously shown that commensal populations of the two subspecies can discriminate on the basis of urinary signals. MUPs are predominant urinary proteins that protect pheromones from rapid degradation in a hydrophilic environment, and individuals of M. m. musculus tend to rely on these urinary cues in the process of subspecies discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 35 publications
8
53
2
Order By: Relevance
“…Because MUPs represent substantial investment in excreted protein, we hypothesized that increased mating success and decreased survival in promiscuous-line males could be associated with up-regulated MUP expression. Urine collected from fourth-generation, individually housed adult males following the testosterone assay revealed that promiscuous-line males had higher MUP expression than monogamous-line males ( To identify specific up-regulated Mup loci in promiscuous-line males, we used reverse transcription quantitative qPCR (rt-qPCR) with nine primer sets from published studies that amplify most Mup transcripts (19,29) (Table S1). Because of extremely high sequence identity, some primer pairs were able to discriminate only subsets of paralogous Mup loci (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because MUPs represent substantial investment in excreted protein, we hypothesized that increased mating success and decreased survival in promiscuous-line males could be associated with up-regulated MUP expression. Urine collected from fourth-generation, individually housed adult males following the testosterone assay revealed that promiscuous-line males had higher MUP expression than monogamous-line males ( To identify specific up-regulated Mup loci in promiscuous-line males, we used reverse transcription quantitative qPCR (rt-qPCR) with nine primer sets from published studies that amplify most Mup transcripts (19,29) (Table S1). Because of extremely high sequence identity, some primer pairs were able to discriminate only subsets of paralogous Mup loci (29).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have proposed that such expression is a result of sexual selection. This "honest-signal" model predicts that females favor males who can afford high expression despite potential costs (e.g., protein loss or attracting predators and competitors) (18)(19)(20)(21)(22). Although this hypothesis has not been explicitly tested, the observation that MUP concentration declines as mice adapt to captivity (17,23) suggests a possible role of relaxed social and sexual selection.…”
mentioning
confidence: 99%
“…In one prominent example, distinctive profiles of MUPs are expressed in different strains, as well as in different subspecies, of mice (Robertson et al 1996;Stopková et al 2007). An atypical MUP that preferentially binds to 2-sec-butyl-4,5-dihydrothiazole is male-specific (Armstrong et al 2005).…”
Section: Mhc Odourtypes and Complexity Of Individual Odour Signaturesmentioning
confidence: 99%
“…This could be a starting point to determine how these proteins evolve through speciation (Hiadlovska et al, 2013), and their potential influence on sub-species recognition Ganem, 2002, 2008) and aggression (Dureje et al, 2011). These two sub-species have been previously found to vary quantitatively in the abundance of male VOCs (MucignatCaretta et al, 2010) and MUP expression between sexes (Stopková et al, 2007) with differences in the beta-barrel residues under selection (Karn and Laukaitis, 2012). Thus, we have identified new members of the odorant binding protein family and focused on the level and locations of expression of soluble lipocalins.…”
mentioning
confidence: 98%
“…Volatiles specifically bind to receptors of chemosensory neurons when released (Tirindelli et al, 1998;Novotny, 2003). In mice, the functions of lipocalin transporters are not well understood and most studies focused on the major urinary proteins (MUPs), which are expressed in the liver and transport volatile odor/organic compounds (VOCs) to the urine (Shahan and Derman, 1984;Shahan et al, 1987a,b;Stopková et al, 2007). MUPs have also been reported to be expressed in several tissues other than the liver (Shaw et al, 1983;Shahan et al, 1987a;Cavaggioni et al, 1999;Utsumi et al, 1999;Karn and Laukaitis, 2011), though their functions are not understood.…”
mentioning
confidence: 99%